Production of hesperetin using a covalently multipoint immobilized diglycosidase from Acremonium sp. DSM24697 - Piñuel, Maria Lucrecia (2013)
The diglycosidase α-rhamnosyl-β-glucosidase (EC 3.2.1.168) from the fungus Acremonium sp. DSM24697 was immobilized on several agarose-based supports. Covalent multipoint immobilization onto glyoxyl-activated agarose was selected as the more stable preparation at high concentration of dimethyl sulfoxide (DMSO) and high temperature. The optimal conditions for the immobilization process involved an incubation of the enzyme with agarose beads containing 220 μmol of glyoxyl groups per gram at pH 10 and 25°C for 24 h. The hydrolysis of hesperidin carried out in 10% v/v DMSO at 60°C for 2 h reached 64.6% substrate conversion and a specific productivity of 2.40 mmol h-1 g-1. Under these conditions, the process was performed reutilizing the catalyst for up to 18 cycles, maintaining >80% of the initial activity and a constant productivity 2.96 ± 0.42 µmol-1 h-1 g-1. To the best of our knowledge, such productivity is the highest achieved for hesperetin production through an enzymatic approach.